(untitled) (The Shivapuri Journal, 2026)
The National Security Council (NSC) plays a critical role in addressing national security and foreign policy through a holistic lens. Established first in United States in response to the coordination challenges faced during World War II, similar councils emerged in the United Kingdom, India, Israel, and Mongolia, aimed at ensuring comprehensive national security. In Nepal, the NSC was created to bring the military under civilian oversight and has since evolved, with its role significantly expanded following constitutional reforms in 2015. This study conducts a comparative analysis of the NSCs in the aforementioned countries alongside Nepal’s NSC, utilizing insights from key informant interviews with former officials. The findings reveal notable structural and functional gaps within Nepal’s NSC in comparison to its counterparts. It advocates for critical reforms, including the appointment of a National Security Adviser, an increase in membership as necessary, an enhanced secretariat with specialized expertise, and a broadening of the NSC’s mandate to encompass foreign policy and economic decision-making. The proposed changes emphasize the need for initial reforms followed by comprehensive restructuring, including constitutional amendments to ensure efficacy and adaptability in an evolving security landscape. These improvements are essential for strengthening governance and resilience within Nepal’s national security framework.